IDENTIFICAÇÃO DE UM SISTEMA DE LODO ATIVADO DE PEQUENA ESCALA DESENVOLVIDO EM LABORATÓRIO - Lima, Freud Sebastian Bach Carvalho (2011)
In activated sludge systems, the dissolved oxygen is used by microorganisms to decompose organic matter and treatment of wastewater. In these systems the dynamics of dissolved oxygen has been seen as the main source of information to obtain online information about the treatment process. Thus, the development of an appropriate model for the dynamics of dissolved oxygen and estimation of the parameters of this model can improve the quality of the estimates of process parameters and, consequently, the measurement system. In this study, a model of the bench-scale reactor is developed considering the dynamics associated with the operation of the aeration system and the dissolved oxygen sensor. The aeration system consists of air pumps with two operating states: on or off, and dissolved oxygen measurement is made by electrochemical cell based on Clark. Approach was used identification systems in continuous time and state variable filters with the least squares estimator for estimating the parameters of the model developed. Simulations and experimental results, using a bench scale reactor developed in the laboratory, are presented to illustrate the proposed model.